2013
DOI: 10.4103/0019-5413.106900
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of subvastus approach in elderly nonobese patients undergoing bilateral simultaneous total knee arthroplasty: A randomized controlled study

Abstract: Background:Subvastus approach in total knee arthroplasty (TKA) spares the quadriceps and may assist in faster rehabilitation. The present randomised controlled study was conducted to determine if the subvastus approach results in early recovery, faster mobilization, shorter hospital stay, and improved function.Materials and Methods:100 patients undergoing simultaneous bilateral TKA were randomized into two groups: subvastus group and medial parapatellar group. The patients were assessed clinically using VAS, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
(28 reference statements)
0
25
0
Order By: Relevance
“…There is only one study in which these two approaches have been compared in SBTKA patients. 22 This study was on the elderly (>70 years), nonobese patients and found that SVA decreases hospital stay and pain scores in the select group of patients. However, this study analyzed patients only till day of discharge and did not follow up the patients on short-or long-term basis.…”
Section: Discussionmentioning
confidence: 95%
“…There is only one study in which these two approaches have been compared in SBTKA patients. 22 This study was on the elderly (>70 years), nonobese patients and found that SVA decreases hospital stay and pain scores in the select group of patients. However, this study analyzed patients only till day of discharge and did not follow up the patients on short-or long-term basis.…”
Section: Discussionmentioning
confidence: 95%
“…After removing 165 duplicates, 258 studies were reserved for abstract screening and full-text screening. Finally, nineteen RCTs [ 12 , 14 , 16 , 18 26 , 30 – 36 ] were considered to be eligible for meta-analysis. Of the included studies, nine [ 14 , 17 , 19 , 22 , 31 – 35 ] RCTs comparing the quadriceps-sparing approach with the standard parapatellar approach and ten [ 12 , 16 , 18 , 20 , 21 , 23 26 , 30 ] comparing the subvastus approach with the standard parapatellar approach were included.…”
Section: Resultsmentioning
confidence: 99%
“…Ten RCTs [ 12 , 16 , 18 , 20 , 21 , 23 26 , 30 ] comparing the subvastus with the standard parapatellar approach were included for meta-analysis (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Jain, et al . compared a series of cases of TKA operated by medial parpatellar approach and subvastus approach and found later approach superior interm of pain relief and postoperative mobilization 15. Sancheti et al .…”
Section: Submissionmentioning
confidence: 99%